1978
DOI: 10.1007/bf01944222
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid ordering and state of aggregation in lymphocyte plasma membranes after exposure to mitogens

Abstract: An electron spin probe study was made of the effect of a number of mitogenic agents on the ordering and state of aggregation of the plasma membrane lipids of lymphocytes. These agents, which included phytohemagglutinin, Concanavalin A, the calcium ionophore A23187 and periodate, caused a 20% decrease in lipid ordering in the region of the bilayer probed by 5-nitroxide stearic acid. The corresponding methyl ester probe showed marked probe-probe interaction under the same conditions indicating an aggregation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

1980
1980
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 46 publications
6
32
1
Order By: Relevance
“…This change in fatty acid composition is accompanied by an increase in membrane fluidity (Anel et al 1990;Calder et al 1994b), although this has been a controversial subject for many years (for references, see Calder et al 1994b). In support of the proposal that membrane fluidity changes are an inherent component of lymphocyte activation and subsequent proliferation (Anel et al 1990;Calder et al 1994b), Curtain et al (1978) found that a non-mitogenic lectin (wheatgerm agglutinin) does not affect lymphocyte membrane fluidity, in contrast to the effect of the mitogenic lectins Con A and PHA. That plasma membrane fluidity does influence lymphocyte activity was shown by the studies of Maccecchini & Burger (1977) and Huber et aE.…”
Section: 59mentioning
confidence: 98%
“…This change in fatty acid composition is accompanied by an increase in membrane fluidity (Anel et al 1990;Calder et al 1994b), although this has been a controversial subject for many years (for references, see Calder et al 1994b). In support of the proposal that membrane fluidity changes are an inherent component of lymphocyte activation and subsequent proliferation (Anel et al 1990;Calder et al 1994b), Curtain et al (1978) found that a non-mitogenic lectin (wheatgerm agglutinin) does not affect lymphocyte membrane fluidity, in contrast to the effect of the mitogenic lectins Con A and PHA. That plasma membrane fluidity does influence lymphocyte activity was shown by the studies of Maccecchini & Burger (1977) and Huber et aE.…”
Section: 59mentioning
confidence: 98%
“…Of importance, the n -6/n -3 ratio, which was approx. 10 in the control cells, was significantly increased by culture in the presence of linoleic or arachidonic acids and significantly decreased by culture in the presence of n -3 PUFA (Table 6). …”
Section: C3lmentioning
confidence: 99%
“…The dry fihn of spin label was obtained by transferring 10 1 of a 1 mg/ml solution of 5-DOXYL-stearic acid in chloroform to a small glass tube and evaporating to dryness. The spin-labelled lymphocyte suspension was transferred to a 100,tl glass capillary tube with a sealed end.…”
Section: Plasma-membrane Fluldity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin resonance analysis of HIV and intact, uninfected HUT-78 cells revealed that the viral envelope was approximately 11% more ordered than the lymphocyte (5). Since earlier studies of 5-NS-labeled lymphocytes indicated that this probe most likely resided in the plasma membrane and did not penetrate into intracellular membranes (47,48), we interpreted our analysis of intact cells to indicate that the spin probe was reporting the milieu of the surface membrane only. However, spectral contributions of the probe residing within intracellular membranes (i.e., a composite spectrum) could not be ruled out, since purified plasma membranes were not previously analyzed (5).…”
mentioning
confidence: 99%